Carlos Fernández y Valentino Gianuzzi, César Vallejo. Textos rescatados. Editorial Universitaria, Lima, 2009. - Cajero Vázquez, Antonio (El Colegio de México, 2011)
Se reseña el libro:César Vallejo. Textos rescatados.